DINAMIKA PENDIDIKAN ISLAM PASCA KEMERDEKAAN DI INDONESIA - Jafarul Musadad, Ahmad (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2021)
Abstract: Islamic education was originally a scientific base that first appeared in the archipelago (Nusantara). Pesantren is the oldest education recorded in history books, and at the same time has an important role in the development of Islamic education, no exception after Indonesia gained independence from the colonial reign. Although independence has been achieved, Indonesian education cannot be said to be smooth in its journey, in this case the following article will discuss the dynamics of post-independence Islamic Education related. Regarding the old order, Islamic education had existed before, and it was mostly pesantren, and public schools, but it was not yet neatly arranged, however in this period there were many laws and regulations related to policies, to carry out religious teaching. Then, entering the new order, education only focuses on formal education, while informal and Islamic education become stepchildren of the government. When entering the era of reform, a lot of Islamic education began to grow and develop into various teachings, one of them is madrasa as well as the education of Al-Qur'an and so on. This research uses the historical method which consists of four stages, namely heuristics (source gathering stage), external criticism (determining source authenticity) and internal criticism (determining source credibility), interpretation (analysis) of data, and historiography (writing process). The results of this study stated that post-independence Islamic education in Indonesia gave birth to ups and downs in policy and ended with the number of institutions that developed pesantren education, as the oldest educational system.Abstrak: Pendidikan Islam pada mulanya merupakan basis keilmuan yang pertama kali muncul di Nusantara (Nusantara). Pesantren merupakan pendidikan tertua yang tercatat dalam buku-buku sejarah, dan sekaligus memiliki peran penting dalam perkembangan pendidikan Islam, tidak terkecuali setelah Indonesia merdeka dari penjajahan. Meski kemerdekaan telah tercapai, namun perjalanan pendidikan Indonesia tidak bisa dikatakan mulus, dalam hal ini artikel berikut akan membahas terkait dinamika Pendidikan Islam pasca kemerdekaan.Pada masa orde lama, pendidikan Islam sudah ada sebelumnya, kebanyakan pesantren, dan sekolah umum, namun belum tertata dengan rapi, namun pada masa ini banyak peraturan perundang-undangan yang terkait dengan kebijakan, untuk menjalankan ajaran agama. Kemudian memasuki orde baru, pendidikan hanya menitikberatkan pada pendidikan formal, sedangkan pendidikan informal dan Islam menjadi anak tiri pemerintah. Memasuki era reformasi, banyak pendidikan Islam yang mulai tumbuh dan berkembang menjadi berbagai ajaran, salah satunya madrasah serta pendidikan Al-Qur’an dan sebagainya. Penelitian ini menggunakan metode sejarah yang terdiri dari empat tahapan, yaitu heuristik (tahap pengumpulan sumber), kritik eksternal (menentukan keaslian sumber) dan kritik internal (menentukan kredibilitas sumber), interpretasi (analisis) data, dan historiografi (proses penulisan). Hasil penelitian ini menyatakan bahwa pendidikan Islam pasca kemerdekaan di Indonesia melahirkan pasang surut kebijakan dan diakhiri dengan banyaknya lembaga yang mengembangkan pendidikan pesantren, sebagai sistem pendidikan tertua.